Administration of Rhodiola kirilowii Extracts during Mouse Pregnancy and Lactation Stimulates Innate but Not Adaptive Immunity of the Offspring - Sławomir Lewicki; Ewa Skopińska-Różewska; Aleksandra Brewczyńska; Robert Zdanowski (Journal of Immunology Research)
The use of antibiotics during pregnancy and lactation is associated with an increased risk of developmental disorders. One of the natural medicinal plants—Rhodiola kirilowii, widely used as an immunostimulant in adults—might be a good alternative to antibiotic treatment. The aim of present study was to assess whether daily oral administration of 20 mg/kg of Rhodiola kirilowii aqueous (RKW) or 50% hydroalcoholic (RKW-A) extracts affected hematological and immunological parameters of 6-week-old mouse progeny. There was no significant change in hematological parameters of blood with the exception of hemoglobin, which was significantly higher (about 4%) in RKW group. Offspring of mothers fed Rhodiola kirilowii extracts had increased percentage of granulocytes and decreased percentage of lymphocytes. These changes correlated with decreased percentage of CD3+/CD4+ T-cells (RKW and RKW-A), decrease of CD8+ cells, and increase percentage of NK cells in RKW group. In addition, both types of Rhodiola kirilowii extracts stimulated granulocyte phagocytosis and increased level of respiratory burst. In conclusion, the long-term supplementation of mouse mothers during pregnancy and lactation with RKW or RKW-A extracts affects the immune system of their progeny. These results should be taken into consideration before administration of Rhodiola kirilowii to pregnant and lactating women.